An exploratory study investigating the impact of a differentiate framework of instruction on generalist teachers perceived confidence to teach visual arts - Eddles-Hirsch, Katrina (Journal of University Teaching and Learning Practice, 2017)
This article reports on an exploratory study that addressed the low confidence levels of 80 generalist primary student teachers enrolled in a mandatory visual arts course. Previous studies in this area have found that a cycle of neglect exists in Australia, as a result of educators’ lack of confidence in their ability to teach visual arts. This is believed to create a knock on effect whereby generalist primary student teachers enter mandatory tertiary visual arts units with little belief in their own art ability. This exploratory study centred on proactively applying the Tomlinson Model of differentiation in an effort to raise student confidence levels. By providing students with multiple avenues to access essential course understandings, students’ perceptions to teach visual arts changed significantly by course completion. This research has significance as there is a paucity of research re the implications of implementing a differentiated model of instruction at the tertiary level